Desenvolvimento de bebida vegetal de coco (Cocos nucifera L.) fermentada por grãos de kefir: análises físico-químicas, microbiológicas, sensoriais e suas aplicações gastronômicas - Rios, Renato de Mesquita (2024)
Academic studies about food and fermentation processes have increased significantly, aiming to understand transformations, standardize them and develop new products and uses for foods, often the ancient one. Several foods pass through fermentation process, such as bread, wine, beer, and cheese, but few maintain as many viable microorganisms after the process as yogurt, kombucha and kefir. Kefir is a symbiosis of microorganisms, often cultivated by hand and with several positive effects associated with consumption. Milk is commonly used as a substrate, however, other substrates, mainly of vegetable origin, have been used to ferment kefir grains. This research aimed to propose the production of a coconut vegetable drink fermented by kefir grains in four different fermentation times (12, 24, 36 and 48 hours) for gastronomic uses. The samples were subjected to physicochemical analyzes (pH, titratable acidity, color and CO2) and to counts of total lactic acid bacteria, yeasts and mesophilic aerobes. Sensory analysis was also carried out using a balanced hedonic scale with nine points to determine the acceptance of the attributes appearance, aroma, flavor and overall impression; another one, with five points, to assess purchase intention; Also it was used the Check-All-That-Apply (CATA) and Rate-All-That-Apply (RATA) methods to evaluate which terms were related to the samples and the degree of intensity of these terms. The pH decreased and the soluble acidity increased up to 36 hours of fermentation (averages of 3.75 and 3.3%, respectively), followed by stability, as well as CO2 production, which rose to 1.92 g/100 mL and stabilized. Microbiological analysis confirmed the adaptability of the microorganisms present, suggesting a possible increase in their count in longer fermentative processes. In the end, there was a predilection for the 12-hour fermentation sample, but the 24-hour sample would carry a higher positive microbial load without a significant difference in preference from the previous one. It is possible to articulate the gastronomic use of other samples depending on the preparation proposal, since thinking of Gastronomy as an expanding field of knowledge means understanding that there are countless possibilities for using products resulting from innovative processes.